Feasibility of a Dual-Fuel Engine Fuelled with Waste Vegetable Oil and Municipal Organic Fraction for Power Generation in Urban Areas. (3rd July 2012) - De Simio, L.; Gambino, M.; Iannaccone, S.
Abstract : Biomass, in form of residues and waste, can be used to produce energy with low environmental impact. It is important to use the feedstock close to the places where waste are available, and with the shortest conversion pathway, to maximize the process efficiency. In particular waste vegetable oil and the organic fraction of municipal solid waste represent a good source for fuel production in urban areas. Dual fuel engines could be taken into consideration for an efficient management of these wastes. In fact, the dual fuel technology can achieve overall efficiencies typical of diesel engines with a cleaner exhaust emission. In this paper the feasibility of a cogeneration system fuelled with waste vegetable oil and biogas is discussed and the evaluation of performance and emissions is reported on the base of experimental activities on dual fuel heavy duty engine in comparison with diesel and spark ignition engines. The ratio of biogas potential from MSW and biodiesel potential from waste vegetable oil was estimated and it results suitable for dual fuel fuelling. An electric power installation of 70 kW every 10, 000 people could be achieved.